Analysis of Low Back Pain Prevention Strategies Based on Work Environment and Attitude Evaluation of Back Office Employees - Mela Ardeline; Tarif, Eqiu Alkahfi; Malik, Yogi Septian (Journal of Engineering Science and Technology Management, 2025)
The work environment affects employee health, especially in offices where most employees sit for long periods. One common health issue is lower back pain, which can be caused by poor posture, non-ergonomic chairs and desks, and uncomfortable work settings. Initial observations showed that many employees had improper sitting postures and workstations that did not meet ergonomic standards.This research aimed to identify the factors that cause lower back pain and to find strategies for prevention and treatment. The study was conducted at a health facility using a quantitative method with a cross-sectional approach. A total of 34 back-office employees participated as respondents. Data were collected through a lower back pain questionnaire, the RULA (Rapid Upper Limb Assessment) worksheet to assess work posture, interviews, and field observations.The results showed that 20 employees (58.82%) experienced lower back pain. Factors that contributed to this condition included age, length of service, physical workload (EMK), and work posture. Among these, work posture was found to be the most significant factor (p = 0.022).To reduce lower back pain among employees, several strategies were suggested: forming an Occupational Health and Safety (OHS) evaluation team, improving the work environment and systems, and providing education about correct posture and back pain prevention. These steps aim to create a healthier work environment and reduce future complaints of back pain.